Ultra-proactive Therapeutic Drug Monitoring of Infliximab Based on Point of Care Testing in Inflammatory Bowel Disease: Results of a Pragmatic Trial. (23rd July 2021) - Bossuyt, Peter; Pouillon, Lieven; Claeys, Sophie; D'Haens, Soetkin; Hoefkens, Eveline; Strubbe, Beatrijs; Marichal, Denis; Peeters, Harald
Abstract: Background: With point of care testing [POCT] for infliximab [IFX], ultraproactive therapeutic drug monitoring [TDM] with ad-hoc dose optimisation is possible in patients with inflammatory bowel disease [IBD]. Aim: To compare the clinical outcomes of an ultraproactive TDM algorithm of IFX based on POCT with reactive TDM in patients with IBD, in a pragmatic clinical trial. Methods: All patients with IBD and maintenance IFX treatment were included between June and August 2018 in two centres. Centre A applied an ultra-proactive TDM algorithm incorporating POCT, and centre B applied reactive TDM. Primary endpoint was failure of IFX therapy after 1 year. Secondary endpoints included sustained clinical remission and mucosal remission. Results: In total 187 patients [ n = 115/72 cohort A/B] were included. Cohort A had more trough level [TL] measurements compared with cohort B [8.8 vs 1/patient/year; p <0.0001], leading to a significant higher number of dose optimisations. POCT testing was required in 27% after the first round of ultra-proactive TDM and in a mean of 6.3% (standard deviation [SD] 1.9) in the subsequent rounds. Ad-hoc extra dosing was needed in 13% of the POCT. After 1 year, no difference was seen between cohort A and cohort B in IFX failure [19% vs 10%; p = 0.08], nor in sustained clinical remission [75% vs 83%; p = 0.17]. Mucosal remission was evaluated in 71 patients [38%], and was more frequent in the reactive TDM cohort [ p = 0.02]. Conclusions: Ultra-proactive TDM in patients with IBD and maintenance IFX treatment leads to equal clinical outcomes as reactive TDM after 1 year of follow-up.